Programmable Calculators and Models - Truong, Melvin, author 645090 (Delhi, India : Research World, 2012)
Programmable calculators are calculators capable of being programmed much like a computer. Since the early 1990s, most of these flexible handheld units belong to the class of graphing calculators. Before the mass-manufacture of inexpensive dot-matrix LCD displays, however, programmable calculators usually featured a one-line numeric or alphanumeric display. Programmable calculators allow the user to write and store programs in the calculator in order to solve difficult problems or automate an elaborate procedure. Programming capability appears most commonly (although not exclusively) in graphing calculators, as the larger screen allows multiple lines of source code to be viewed simultaneously (i.e., without having to scroll to the next/previous display line). Originally, calculator programming had to be done in the calculator's own command language, but as calculator hackers discovered ways to bypass the main interface of the calculators and write assembly language programs, calculator companies (particularly Texas Instruments) began to support native-mode programming on their calculator hardware, first revealing the hooks used to enable such code to operate, and later explicitly building in facilities to handle such programs directly from the user interface. Many programs written for calculators can be found on the internet. Users can download the programs to a personal computer, and then upload them to the calculator using a specialized link cable, infrared wireless link or through a memory card,. Sometimes these programs can also be run through emulators on the PC. One possibility arising from the above is writing interpreters, compilers, and translator programmes for additional languages for programming the machines; BBC Basic has already been ported to the TI 83 and 84 series and other on-board languages and programming tools discussed by many include Fortran, awk, Pascal, Rexx, perl, Common Lisp, Python, tcl, and various Unix shells. Commonly available programs for calculators include everything from math/science related problem solvers to video games, as well as so-called demos. Much of this code is user-created freeware or even open source, though commercial software, particularly for educational and science/engineering markets, is also available.